Integrating Forecasting & Planning Management for Sustainable Hospital Supply Chains and Societal Advancement - Islam, Shaiful; Habib, Md. Mamun (International Journal of Supply Chain Management, 2024)
This research investigates the critical interplay between Forecasting Planning Management (FPM) and Sustainable Hospital Supply Chain Management (SHSCM), exploring their collective impact on Sustainable Societal Advancement (SSA). Anchored on a sample size of 401, the study employs IBM SPSS for factor analysis and IBM AMOS for structural equation modeling, ensuring the reliability and validity of the results. Two hypotheses form the backbone of this research: Firstly, the study hypothesizes a significant relationship between FPM and SHSCM. Secondly, it posits a consequential link between SHSCM, invigorated by Collaborative Information Flow (CIF), and SSA. Both hypotheses are substantiated with robust empirical evidence, indicating positive impacts. The research unravels the pivotal role of FPM in enhancing hospital supply chain sustainability, highlighting its significant influence on SHSCM. This relationship is vital for efficient resource allocation, cost efficiency, and overall sustainability in hospital operations. The study further delves into the transformative effect of SHSCM on broader societal well-being, emphasizing its substantial positive influence on SSA. The findings suggest that sustainable practices within hospital supply chains extend beyond immediate healthcare benefits to broader societal and environmental impacts, contributing to economic stability, environmental conservation, and enhanced public health. Methodologically, the study adopts a comprehensive approach, utilizing factor analysis to validate the reliability of survey responses and structural equation modeling to assess the interrelations among FPM, SHSCM, and SSA. The research's adherence to established validity and reliability criteria is evident in the satisfactory factor loading scores, the KMO measure, and Cronbach's alpha coefficients. While affirming the proposed hypotheses, the study also acknowledges its limitations, particularly its focus on the hospital sector in Bangladesh, which may affect the generalizability of the findings. Furthermore, the cross-sectional nature of data collection points to the potential for longitudinal studies to better comprehend the temporal dynamics of these relationships. The study concludes with a call for future research to broaden the geographic scope and incorporate diverse healthcare settings, thus enriching the global understanding of these dynamics. Additionally, it suggests exploring the integration of digital innovations in FPM and SHSCM to further optimize supply chain processes and enhance sustainability. Overall, this research contributes significantly to the field of sustainable healthcare management, offering empirical evidence on the importance of forecasting and planning in healthcare supply chains and their broader societal implications. It paves the way for healthcare practitioners, policymakers, and researchers to foster sustainable practices in hospital supply chains, ultimately aiming for societal well-being and global health advancements.